PENGARUH PAPARAN CAHAYA TERANG TERHADAP KONDISI FISIOLOGIS PASIEN YANG DIRAWAT DI RUANG ICU - Nabilla Oktaviani Nurlitasari; Dian Hudiyawati (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
Background: Patients in the ICU are exposed to 24 hours of light exposure to abnormally low light levels during the day and constant light disturbances throughout the night. Prolonged abnormal light exposure can impact the circadian rhythm, which may indirectly affect the patient's physiological condition. Objectives: This literature review aims to determine the effect of light exposure on the physiological condition of patients in the ICU, including heart rate, mean arterial pressure (MAP), body temperature and sleep quality and offer possible alternative options. Methods: Qualitative synthesis by collecting research articles for the last five years from Google Scholar, Science Direct, Scopus, Medline, CINAHL, PubMed, and ProQuest. Results: There were 5 international journals with experimental and observational research designs. Abnormal light exposure in the ICU has an effect on increasing the heart rate and decreasing the quality of sleep of the patient. Conclusion: Compared to a decrease in nighttime light levels, an increase in artificial light during the day may be more promising to support the improvement of the patient's physiological condition.